Brief version of Zarit Burden Interview (ZBI) for burden assessment in older caregivers - Gratão, Aline Cristina Martins (Dement Neuropsychol, 2019)
The degree of burden related to the demands of daily care provided to a dependent older adult is important to evaluate due to the negative influence exerted on caregivers’ physical and psychological health. OBJECTIVE: To analyze the validity of the 12-item version of the Zarit Burden Interview administered to older caregivers of community-dwelling older dependent individuals and suggest a cut-off score based on quartiles. METHODS: Three hundred and forty-one older caregivers (mean age: 69.6±7.1 years; 76.8% women) registered with primary healthcare centers were evaluated using the ZBI-12. Additional evaluations addressed stress (Perceived Stress Scale [PSS]), depressive symptoms (Geriatric Depression Scale [GDS]) in the older caregivers and the degree of dependence of the older care recipients (Lawton and Brody [L&B]). RESULTS: Cronbach’s alpha demonstrated very good internal consistency (α=0.81). Correlations were found between all ZBI-12 items and overall score on the PSS (r=0.53; p<0.01). GDS (r=0.43; p<0.01) and L&B (r= -0.23; p<0.01) scale scores. The PSS demonstrated the strongest correlation with ZBI-12 score and proved to be the standard reference. Based on caregivers with a higher degree of stress considering the PSS score quartiles, a cut-off score of 13 points on the ZBI-12 is suggested for screening burden in community-dwelling older caregivers, but should not be assumed as normative data. CONCLUSION: The ZBI-12 can be considered valid for evaluation of burden in clinical practice and research as a fast, efficient option for screening burden among older caregivers of community-dwelling older adults.